Effects of Raw Material (Degraded Solar Dried Banana) on Physical, Chemical and Microbiological Characteristics of Solar Dried Banana Syrup - ทัศนอุดม อรรณพ; สระพินครบุรี วรรณภา; ฉัตรดํารง วาสนา (KKU Science Journal, 2014)
The objectives of this study were to compare the raw material qualities (degraded solar dried banana) of four experimental samples (different storage times at 4 oC), and to evaluate the optimal storage times of degraded solar dried banana for banana syrup production. The physical, chemical and microbiological qualities of raw materials which stored for 4 different storage times (7, 14, 21 and 30 days) at 4oC were significantly different (P≤0.05). The results showed the color, moisture content, total acidity (lactic acid), the microbial quantities such as total count, yeast and mold count and lactic acid bacteria were increasing when the storage time was increased. However, total soluble solid (TSS), and pH were decreasing. Four samples of solar dried banana syrup were obtained by extraction of solar dried bananas with added pectin digested enzymes. The yield of those were ranging from 30.49–32.67% (v/w) and its qualities were significantly different (P≤0.05). L*, b* values and pH were determined ranging from 7.48–13.1, 1.40–3.59 and 3.80–4.49 respectively. Consequently, solar dried banana syrups contained 2.22–4.27, 2.49–3.66 and 1.85–3.66 log CFU/ml of total count, yeast and mold and lactic acid bacteria respectively. In the conclusion, degraded solar dried banana exhibited good potential as substrate for banana syrup production; however, it should not be stored more than 21 days.